Morphological Variability of a Natural Population of Cyanobacterium Raphidiopsis raciborskii in a Temperate Floodplain Lake - Filip Stević; Melita Mihaljević; Dubravka Špoljarić Maronić; Tanja Žuna Pfeiffer; Vanda Zahirović (Taxonomy)
The freshwater cyanobacterium Raphidiopsis raciborskii is an invasive species that was originally described as tropical and is now widely distributed in temperate regions. The current taxonomic position was established based on a multilevel approach with the morphological description of natural populations as well as their ultrastructural, physiological and molecular characterization. The practical problem in identifying this species is that the morphology of the trichome in the natural environment can vary considerably during population growth. The aim of this study was to investigate the morphological variability of R. raciborskii during its blooming in a temperate floodplain lake on the Middle Danube (Europe). In both cases, only straight trichomes were found. Young trichomes with one or two acuminate ends and without heterocytes, referred to as primary filaments, can be exclusively monodominant at the beginning of bloom formation and remain dominant throughout the year, leading to taxonomic confusion. In mature populations, the different morphological forms of secondary filaments may differ in the size of the filaments and in the number and size of akinetes and heterocytes formed in the trichomes. The correct taxonomic identification and early detection of R. raciborskii in natural freshwaters is extremely important for the successful control of the spread of this potentially toxic species.